Prognostication of Concrete Characteristics with Coconut Shell as Coarse Aggregate Partial Percentile Replacement - Deepak, Tirumishi Jada; Jalam, A. A.; Loh, Eric; Siow, Yun Tong; Nair, Sudesh; Panjehpour, Mohammad (International Journal of Scientific Research in Science, Engineering and Technology, 2015)
In this constructed environment, the rising cost of building construction materials is the issue of great concern. The prices of building materials are rising day by day. The coarse aggregates are the main ingredients of concrete. In this paper, the utilization of coconut shell as a replacement for coarse aggregate has been discussed based on the results obtained from comprehensive experimental results. The construction industry totally relies on cement, sand and aggregates for the production of concrete. Properties of concrete with coconut shells (CS) as aggregate partial percentile replacement were studied. Control concrete with normal aggregate and CS concrete with 10 - 50% coarse aggregate replacement were prepared with constant water – binder ratio of 0.45. For all mixes, workability, density, water absorption, compressive strength flexural strength and tensile strength were determined at 7, 14 and 28 days. The results showed a steady decline in the workability. The density results for concrete cube and beam specimens shows general decrease in physical property due to CS replacement. The water absorption tests showed that the percentage water absorption increases with increase in the percentage replacement level of coarse aggregate with CS. The compressive, flexural and tensile strength of CS concrete were found to be lower than normal concrete